Pengaruh Pelatihan, Motivasi, dan Lingkungan Kerja Terhadap Produktivitas Karyawan Pada PT. Angkasa Pura Indonesia Bandar Udara Internasional Soekarno-Hatta - Kintan Ulyantiputeri; Masruri Masruri; Abdillah Sani (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of training, motivation, and work environment on employee productivity at PT. Angkasa Pura Indonesia (Persero), Soekarno-Hatta International Airport. In the increasingly competitive aviation industry, improving human resources is essential to support company performance. The research employed a quantitative method with an associative approach. The sample consisted of employees selected using simple random sampling. The research instrument was a questionnaire tested for validity and reliability, and the data were analyzed using multiple linear regression. The results show that training, motivation, and work environment have a positive and significant effect on employee productivity, both partially and simultaneously. These findings indicate that better training programs, higher work motivation, and a more conducive work environment lead to improved employee productivity. The practical implication highlights the importance for management to strengthen continuous training programs, establish effective reward and incentive systems, and create a healthy work atmosphere. This study is expected to serve as a reference for PT. Angkasa Pura Indonesia (Persero) and other companies in the same sector in formulating human resource development strategies to enhance competitiveness